Identification of a major genetic determinant of glycaemic index in rice - Fitzgerald, M.A.; Rahman, S.; Resurreccion, A.P.; Concepcion, J.; Daygon, V.D.; Dipti, S.S.; Kabir, K.A.; Klingner, B.; Morell, M.K.; Bird, A.R. (Springer, 2011)
Type II diabetes is a major chronic disease. In developing countries, the prevalence of type II diabetes is increasing enormously. Much research indicates that choice of carbohydrates, particularly those with low glycaemic index (GI) is able to assist in the management or prevention of type II diabetes. Most developing countries consume rice as the staple. The objectives of this study were to determine the variability in the GI of popular improved and traditional varieties of rice and to find the genetic basis of GI. A method to predict GI using an in vitro system was compared to the in vivo system using a range of rice varieties differing in GI. Large variability in GI, ranging from low to high GI, was found using a set of 235 varieties. The major gene that associated with GI in the 235 varieties was the Waxy gene. This paper reports the first large-scale phenotyping of this trait, provides important information for nutritionists to identify and quantify the impact of low GI rices on blood sugar status and offers a mechanism for breeding programmes to select for GI based on amylose content. Furthermore, it allows rice consumers to select particular varieties of rice as their choice of carbohydrate.